Preparation and characterization of blended solid polymer electrolyte 49% poly(methyl methacrylate)-grafted natural rubber:poly(methyl methacrylate)-lithium tetrafluoroborate - Su'ait M.S.; Noor S.A.M.; Ahmad A.; Hamzah H.; Rahman M.Y.A. (2023)
The preparation and characterization of blended solid polymer electrolyte 49% poly(methyl methacrylate)- grafted natural rubber (MG49):poly(methyl methacrylate) (PMMA) (30:70) were carried out. The effect of lithium tetrafluoroborate (LiBF 4) concentration on the chemical interaction, structure, morphology, and room temperature conductivity of the electrolyte were investigated. The electrolyte samples with various weight percentages (wt. %) of LiBF 4 salt were prepared by solution casting technique and characterized by Fourier transform infrared spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), and electrochemical impedance spectroscopy. Infrared analysis demonstrated that the interaction between lithium ions and oxygen atoms occurred at symmetrical stretching of carbonyl (C=O) (1,735 cm -1) and asymmetric deformation of (O-CH 3) (1,456 cm -1) via the formation of coordinate bond on MMA structure in MG49 and PMMA. The reduction of MMA peaks intensity at the diffraction angle, 2? of 29.5 and 39.5 was due to the increase in weight percent of LiBF 4. The complexation occurred between the salt and polymer host had been confirmed by the XRD analysis. The semi-crystalline phase of polymer host was found to reduce with the increase in salt content and confirmed by XRD analysis. Morphological studies by SEM showed that MG49 blended with PMMA was compatible. The addition of salt into the blend has changed the topological order of the polymer host from dark surface to brighter surface. The SEM analyses supported the enhancement of conductivity with the addition of salt. The conductivity increased drastically from 2.0 to 3.4 10 -5S cm -1 with the addition of 25 wt.% of salt. The increase in the conductivity was due to the increasing of the number of charge carriers in the electrolyte. The conductivity obeys Arrhenius equation in higher temperature region from 333 to 373 K with the pre-exponential factor ? o of 1.2110 -7 S cm -1 and the activation energy E a of 0.46 eV. The conductivity is not Arrhenian in lower temperature region from 303 to 323 K.